The influence of intramolecular cyclization and intermolecular cross-linking on the properties of polimeric networks obtained in the radical polimerization of multifunctional methacrylates - Podgórski, M.; Księżopolski, J. (Polimery, 2010)
Homopolymers and copolymers with methyl methacrylate have been synthesized in the photopolymerization reaction of multifunctional dimethacrylates - glycidyl esters of maleic and fumaric acids. The mechanical and thermal properties of the polymerization products were determined (Figs. 1, 3, 6) and the degrees of unsaturated bond conversion (Fig. 4) were evaluated. Dynamic thermal analysis and HDT measurements were performed (Fig. 5). The degree of structural heterogeneity of the formed polymeric networks was assessed and the influence of the networks on the properties of the final products discussed. The different ways in which cyclization and crosslinking influence selected properties of the networks were also presented. An increased participation of cyclization reactions during the polymerization of the cis geometric isomers of dimethylacrylates was observed.